Are the cut‐offs of the rheumatoid factor and anti‐cyclic citrullinated peptide antibody different to distinguish rheumatoid arthritis from their primary differential diagnoses? - Pineda‐Sic, Rita Angélica; Vega‐Morales, David; Santoyo‐Fexas, Leticia; Garza‐Elizondo, Mario Alberto; Mendiola‐Jiménez, Andrés; González Marquez, Karina Itzel; Carrillo‐Haro, Berenice (International journal of immunogenetics, 2024)
Objective: Rheumatoid factor (RF) and anti‐cyclic citrullinated peptide antibody (anti‐CCP) are commonly used for diagnosis of rheumatoid arthritis (RA), although other rheumatic diseases with arthritis can test positive. This study aimed to determine the cutoff values for RF and anti‐CCP with the best diagnostic performance in a sample of patients with RA, compared with other rheumatic diseases. Methods: This was a descriptive, prospective study. EUROINMMUN enzyme‐linked immunosorbent assays for RF isotypes immunoglobulin (Ig) A (IgA), IgG and IgM and third‐generation assay IgG for anti‐CCP were used in serum samples of patients with RA, other rheumatic diseases and healthy subjects. The cutoff with the best diagnostic performance was determined by the Youden Index and receiver operating characteristic analysis Results: Three hundred and thirty‐two serum samples were analysed. The cutoffs proposed in our population were for RF in RA patients versus other rheumatic diseases, and healthy subjects IgM 135 IU/mL, for each disease, compared with RA, were psoriatic arthritis (Psa) IgA 47.2 IU/mL, clinically suspicious arthralgia (CSA) IgA 39.5 IU/mL, primary Sjögren's syndrome (pSS) IgM 180.6 IU/mL, systemic lupus erythematosus (SLE) IgA 42.6 IU/mL, primary fibromyalgia (pFM) IgM 68.6 IU/mL, osteoarthritis (OA) IgM 48 IU/mL, gout IgM 117 IU/mL and healthy IgM 16.3 IU/mL. For anti‐CCP, in RA patients versus other rheumatic diseases, and healthy subjects 6.95 IU/mL, for each disease, compared with RA, were Psa 6.8 IU/mL, CSA 9.95 IU/mL, pSS 20.7 IU/mL, SLE 6 IU /mL, pFM 11.8 IU/mL, OA 11.9 IU/mL, gout 5 IU/mL and healthy 5 IU/mL. Conclusion: Irrespective of the manufacturer's suggested cutoff, the RA versus differential diagnosis cutoffs must be considered.